(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
This cross-sectional study examined the way government scholarship influences female students from low-income families. This study has described the government scholarships offered in community schools and examined the impact of the scholarship on female student’s academic achievement. The purposive sampling and QUAN-Qual. procedure were employed in this study to choose community schools and study areas. The socio-economic position of parents (who live in slum areas), their caste/ethnic variation (majority of them are Dalit and Janajati), and other factors led to select the study. For the study, all 247 eligible respondents girls from slum dwellings, ages eight to eighteen years were included. Data were gathered using a semi-structured interview schedule and a self-structured questionnaire. The student attendance register was used to identify the respondents. There were mainly two types of scholarships (residential and non-residential). It focused on target groups, including girls. Major incentive providers were the government, municipalities, NGOs, and the private sector and they focused on money, materials, and stationery. Nearly half of the respondents have received scholarships, and two-thirds have decided to use incentives for their studies. The incentive has a positive relationship to increase classroom activities and their educational performance. Nearly one-fourth of students have appealed for increased scholarship amounts, as they cannot cover their total expenses.